Design, Synthesis and Biological Evaluation of 3-Hydrazonoindolin-2-one Derivatives as Novel HIV-1 RNase H Inhibitors - Yiying Zhang; Rao Wang; Yueyue Bu; Angela Corona; Laura Dettori; Enzo Tramontano; Christophe Pannecouque; Erik De Clercq; Shuai Wang; Ge Meng; Fen-Er Chen (Molecules)
Targeting ribonuclease H (RNase H) has emerged as a highly promising strategy for treating HIV-1. In this study, a series of novel 3-hydrazonoindolin-2-one derivatives were designed and synthesized as potential inhibitors of HIV-1 RNase H. Notably, several of these derivatives displayed micromolar inhibitory activity. Among the compounds examined, the hit compound demonstrated potent inhibition of HIV-1 RNase H, boasting a Ki value of 2.31 μM. Additionally, the most potent compound of this general structure exhibited remarkable inhibitory activity, with Ki values of 0.55 μM. Through docking studies, the key interactions of this ligand within the active site of RNase H were uncovered. This novel chemical structure can be regarded as a prospective scaffold for the future development of RNase H inhibitors.